2022
DOI: 10.1186/s13578-022-00854-y
|View full text |Cite
|
Sign up to set email alerts
|

cGAS inhibition alleviates Alu RNA-induced immune responses and cytotoxicity in retinal pigmented epithelium

Abstract: Background The degeneration of retinal pigmented epithelium (RPE) cells results in severe diseases, such as age-related macular degeneration (AMD) that causes blindness in millions of individuals. Results We report that targeting GMP-AMP (cGAMP) synthase (cGAS) alleviates Alu RNA-induced immune responses and cytotoxicity in RPE. We find that the deletion of cGAS in RPE inhibits the Alu RNA-stimulated interferon production. cGAS deficiency also prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Both primary RPE and ARPE-19 cells are capable of inducing IFNB in response to Poly I:C 72 , transfected RNA 73,74 , or poly-dA-dT 74 , a synthetic form of B-DNA [75][76][77] . However, previous work with ARPE-19 cells showed a severely limited interferon response due to transfected dsDNA 74 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both primary RPE and ARPE-19 cells are capable of inducing IFNB in response to Poly I:C 72 , transfected RNA 73,74 , or poly-dA-dT 74 , a synthetic form of B-DNA [75][76][77] . However, previous work with ARPE-19 cells showed a severely limited interferon response due to transfected dsDNA 74 .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work with ARPE-19 cells showed a severely limited interferon response due to transfected dsDNA 74 . The ARPE-19 response to RNA appears dependent on the RNA-sensor RIG-I/DDX58 73,74 . Surprisingly, a clear comparison of the type-I interferon response between primary RPE and ARPE-19 cells infected with HCMV seems to be absent from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that by preventing the activation of NLRP3 inflammasome, the RPE was protected from damage in multiple animal models of AMD and against sterile inflammation damage in mice [ 193 ]. Subsequent studies have shown that Alu RNA can trigger RPE cell death through non-canonical NLRP3 inflammasome signalling via gasdermin D (GSDMD) activation [ 47 , 194 , 195 ].…”
Section: The Contribution Of the Nlrp3 Inflammasome To Amdmentioning
confidence: 99%
“…cGAS is a cytosolic DNA sensor that can detect foreign DNA, and damaged mitochondrial DNA (mtDNA), that activates STING [ 197 ]. While many studies have observed mtDNA damage in AMD lesions, recently, the cGAS-STING pathway has been linked to RPE damage [ 194 , 195 , 198 ]. RPE and photoreceptor death are known to be associated with NLRP3 inflammasome mediated pyropotosis due to GSDMD activation and cGAS signalling [ 47 , 199 , 200 ].…”
Section: The Contribution Of the Nlrp3 Inflammasome To Amdmentioning
confidence: 99%
See 1 more Smart Citation